The Effect of Operational Efficiency, Liquidity, And Profitability on Capital Structure in Manufacturing Companies in the Basic Industry and Chemical Sectors Listed on the Indonesia Stock Exchange for the Period 2021-2023 - Khairunnisa, Nabila; Astarani, Juanda (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to evaluate the influence of operational efficiency, liquidity, and profitability on capital structure in manufacturing companies operating in the basic and chemical industry sectors listed on the Indonesia Stock Exchange during the 2021–2023 period. The analysis was conducted using panel data regression, with the Fixed Effect model selected based on the results of the Chow and Hausman tests. The research sample consisted of 32 companies that met the criteria, and data analysis was performed using descriptive and inferential statistical approaches. The findings indicate that operational efficiency does not have a significant impact on capital structure. In contrast, liquidity has a significant negative effect, suggesting that companies with high liquidity levels tend to rely on internal funding sources rather than external financing. Meanwhile, profitability has a significant positive effect on capital structure, indicating that highly profitable firms are more likely to opt for external financing. The regression model used explains 30.89% of the variation in capital structure, with a statistically significant F-statistic. The validity and reliability of the model were confirmed through multicollinearity and heteroscedasticity tests. Overall, the study concludes that operational efficiency does not directly influence capital structure, whereas liquidity and profitability play significant roles in financing decisions. The implications of these findings offer strategic guidance for corporate management in formulating financing strategies based on a company’s liquidity position and profitability level.